Scented Colours: Artistic Interest in the Crossmodal Connection Between Colour and Odour - Charles Spence (Baltic International Yearbook of Cognition, Logic and Communication, 2020)
Artists have long been interested in the crossmodal links that exist between colour and scent. While traditionally envisioned as a kind of synaesthesia, contemporary accounts of the connections between this particular pair of senses have typically focused on explanations in terms of involuntarily-induced crossmodal mental imagery and crossmodal correspondences instead. A large body of empirical research now supports the view that the majority of non-synaesthetic individuals do indeed systematically match colours to odours, via semantic (or source-object based) matching, and/or on the basis of emotional-mediation or perceptual similarity. Universal agreement with regard to the best- matching colours for odours is, however, never obtained. What is more, the consensuality of the crossmodal mappings obtained within groups of individuals (and especially across culture, and age) tend to decline when one moves away from semantically- based crossmodal matches. As such, the longstanding aim amongst certain artists to play with the abstract correspondences between scent, colour, and, on occasion, also sound in order to try to deliver universally-meaningful crossmodal correspondences seems unlikely ever to be realized. Nevertheless, that does not mean that scent and colour can’t still be linked in intriguing ways, as illustrated by a number of the exhibits at the 2015 Tate Sensorium multisensory exhibition in London.
Keywords: crossmodality